2011
DOI: 10.1111/j.1439-0531.2011.01862.x
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Sperm Storage in the Female Reproductive Tract: an Interspecies Comparison

Abstract: Contents Once semen has been collected for artificial insemination, it is diluted into extenders designed to prevent its deterioration over the period prior to insemination. If the semen is not frozen, the extenders provide protection for a period of a few hours to a few days, depending on species. Despite the efforts of biotechnologists to increase the duration of storage without compromising fertility, there has been relatively little progress for many years. However, comparative studies in diverse species h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
57
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(59 citation statements)
references
References 85 publications
(97 reference statements)
0
57
1
1
Order By: Relevance
“…This strategy contrasts with other species in which direct contact between the spermatozoa and oviductal epithelium suppresses sperm function, and hence facilitates their longterm storage [49]. It has thus been suggested that sperm longevity in the female alligator may be a property of the male gamete [45].…”
Section: Discussionmentioning
confidence: 57%
“…This strategy contrasts with other species in which direct contact between the spermatozoa and oviductal epithelium suppresses sperm function, and hence facilitates their longterm storage [49]. It has thus been suggested that sperm longevity in the female alligator may be a property of the male gamete [45].…”
Section: Discussionmentioning
confidence: 57%
“…Sperm storage after mating is a female reproductive tract phenomenon that has been observed in various animals with the presumed aim to preserving sperm fertilizing capacity in species in which mating and ovulation are poorly synchronized (Holt 2011). In the mare (Bader 1982, Scott et al 2000 and many other mammals (rabbit (Harper 1973), pig (Hunter 1981), sheep (Hunter & Nichol 1983), mouse (Suarez 1987), cattle (Hunter & Wilmut 1984) and hamster (Yanagimachi & Chang 1963)), an oviductal sperm reservoir is established at the uterotubal junction and the caudal part of the oviductal isthmus.…”
Section: Introductionmentioning
confidence: 99%
“…Many organisms have been shown to store sperm inside the female reproductive tract [1]. Some examples include social insects [2], crabs [3], salamanders [4], turtles [5], lizards [6,7], bats [8] and fish [9,10].…”
Section: Introductionmentioning
confidence: 99%